Burden of Stroke in Egypt: Current Status and Opportunities. Issue 8 (December 2014) - Abd-Allah, Foad; Moustafa, Ramez Reda
Middle East and North Africa (MENA) countries have a diversity of populations with similar life style, dietary habits, and vascular risk factors that may influence stroke risk, prevalence, types, and disease burden. Egypt is the most populated nation in the Middle East with an estimated 85.5 million people. In Egypt, according to recent estimates, the overall prevalence rate of stroke is high with a crude prevalence rate of 963/100 000 inhabitants. In spite of disease burden, yet there is a huge evidence practice gap. The recommended treatments for ischemic stroke that are guideline include systematic supportive care in a stroke unit or stroke center is still deficient. In addition, the frequency of thrombolysis in Egypt is very low for many reasons; the major one is that the health insurance system is not covering thrombolysis therapy in nonprivate sectors so patients must cover the costs using their own personal savings; otherwise, they will not receive treatment. Another important factor is the pronounced delay in prehospital and in hospital management of acute stroke. Improvement of stroke care in Egypt should be achieved through multi and interdisciplinary approach including public awareness, physicians' education, and synergistic approach to stroke care with Emergency Medical System.